2016
DOI: 10.1016/j.biopsych.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Medication for Attention-Deficit/Hyperactivity Disorder and Risk for Depression: A Nationwide Longitudinal Cohort Study

Abstract: Background Attention-deficit/hyperactivity disorder (ADHD) is associated with high rates of psychiatric comorbidity, including depression. However, it is not yet clear whether ADHD medication increases or decreases the risk for depression. Methods We studied all individuals born between 1960 and 1998 and diagnosed with ADHD in Sweden (n=38,752). We obtained data for prescription of ADHD medication, diagnosis of depression and other psychiatric disorders, and socio-demographic factors from population-based re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 34 publications
(52 reference statements)
6
90
1
1
Order By: Relevance
“…They extend a finding of associations between stimulant medication and lower risk of substance-related problems in Sweden by demonstrating within-individual associations with not only lower concurrent risk but also lower long-term risk of substance-related events (19). Moreover, accumulating findings have also demonstrated within-individual associations with lower risk for injuries, transport accidents, criminality, depression, and suicide (26, 3136). If these results reflect protective effects, it is possible that differing processes underlie decreased substance-related risk in the short and longer term.…”
Section: Discussionmentioning
confidence: 99%
“…They extend a finding of associations between stimulant medication and lower risk of substance-related problems in Sweden by demonstrating within-individual associations with not only lower concurrent risk but also lower long-term risk of substance-related events (19). Moreover, accumulating findings have also demonstrated within-individual associations with lower risk for injuries, transport accidents, criminality, depression, and suicide (26, 3136). If these results reflect protective effects, it is possible that differing processes underlie decreased substance-related risk in the short and longer term.…”
Section: Discussionmentioning
confidence: 99%
“…184 With mild or moderate cases of depression, treatment of ADHD should be pursued, as it can reduce the long-term risk for depressive episodes. 185 A large study in Taiwan found lower rates of antidepressant resistance when individuals with ADHD and depression received combined treatment with antidepressants and psychostimulants vs treatment with antidepressant alone. 186 However, treatment of depression should take precedent over ADHD when it is the most disabling condition such as in major depressive disorder or suicidal cases.…”
Section: Depressionmentioning
confidence: 99%
“…Since long-term randomized trials are impossible and unavailable due to ethical limitations, recent analyses from registries provide the most convincing evidence on the long-term benefits of methylphenidate. These studies indicate, for example, that treatment with methylphenidate has beneficial effects in terms of important distal outcomes that go beyond symptom control such as a reduction in comorbid depression, substance-use and dependency, trauma-related visits to the emergency room and mortality (Chang et al 2014(Chang et al , 2016Dalsgaard et al 2015;Man et al 2015). Furthermore, in the absence of clinically relevant effects of non-pharmacological treatment options on the core symptoms of ADHD (SonugaBarke et al 2013), a dogmatically biased devaluation of the currently most effective treatment is neither helpful for science nor patients.…”
Section: Resultsmentioning
confidence: 99%